2017
DOI: 10.3389/fpsyt.2017.00143
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Therapy for Obsessive–Compulsive Disorder with and without Autism Spectrum Disorder: Gray Matter Differences Associated with Poor Outcome

Abstract: Cognitive behavioral therapy (CBT) is an effective treatment for obsessive–compulsive disorder (OCD) and is also applicable to patients with both OCD and autism spectrum disorder (ASD). However, previous studies have reported that CBT for patients with both OCD and ASD might be less effective than for patients with OCD alone. In addition, there is no evidence as to why autistic traits might be risk factors. Therefore, we investigated whether comorbidity between ASD and OCD may significantly affect treatment ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…CBT treatment helps OCD patients develop more effective cognitive strategies to adapt to their external and changing environment (Moras, 2006). Previous studies have found that the higher rCBF and regional homogeneity in the left DLPFC decreased after CBT treatment (Yamanishi et al, 2009;Yang et al, 2015), and the abnormalities of grey matter volume in DLPFC negatively affected the CBT outcomes (Tsuchiyagaito et al, 2017). The current study's finding that successful CBT treatment decreased the DC in the left DLPFC indicates that the numbers of voxels across the brain that strongly correlate with the left DLPFC decreased, which may be related to the much lower effort required to control intrusive thoughts and repetitive behavior in OCD patients after CBT.…”
Section: Discussionmentioning
confidence: 99%
“…CBT treatment helps OCD patients develop more effective cognitive strategies to adapt to their external and changing environment (Moras, 2006). Previous studies have found that the higher rCBF and regional homogeneity in the left DLPFC decreased after CBT treatment (Yamanishi et al, 2009;Yang et al, 2015), and the abnormalities of grey matter volume in DLPFC negatively affected the CBT outcomes (Tsuchiyagaito et al, 2017). The current study's finding that successful CBT treatment decreased the DC in the left DLPFC indicates that the numbers of voxels across the brain that strongly correlate with the left DLPFC decreased, which may be related to the much lower effort required to control intrusive thoughts and repetitive behavior in OCD patients after CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that CBT for obsessive-compulsive disorder with ASD is effective [39], but that the response to ERP is relatively poor [14]. The novelty of this study was that the ability to communicate in AQ predicted treatment response.…”
Section: Comparison With Previous Studiesmentioning
confidence: 81%
“…When patients with OCD have poor executive function, they cannot understand their problem or conduct and complete ERP tasks appropriately. A previous brain imaging study showed that abnormalities in the left dorsolateral prefrontal cortex, a region that has been implicated in working memory [43], negatively affect CBT outcomes [14]. Mental flexibility, as measured using the California Verbal Learning Test, was predictive of a good response to CBT; in contrast, it was interesting to note that fluoxetine responsiveness was impaired [44].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a previous randomised controlled trial (RCT) for CBT for co-morbid obsessivecompulsive disorder (OCD) in high-functioning ASD has reported within-group effect sizes of 1.01 for the CBT group (Russell et al, 2013). To summarise the results of previous studies, CBT appears to be effective in treating anxiety in patients with ASD (Perihan et al, 2019;Ung et al, 2015), but less effective in patients without ASD (Tsuchiyagaito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%